Nutritional Care with Cancer Treatment - Singh, Sunder; Dhankhar, Rakesh; Dahiya , Kiran; Ahlawat, Raunak; Gupta, Mohit; Dhankhar, Kumud (New Horizons in Medicine and Medical Research Vol. 12, 2022)
Nutrition and diet play a major role in cancer. Dietary factors are a significant component of the identifiable attributable risks of cancer. Generally, types of nutrition are optimal nutrition and malnutrition. The study is conceptual. The main objective of the study is to explain the optimum nutrition for cancer patients. Malnutrition is also divided into undernutrition and overnutrition. Overnutrition is becoming a more frequently recognized problem in cancer patients. It is an attributable cause of more than 15% of cancer deaths. The nutrition care of cancer patients should focus on the goals of recognizing the presence and/or risk of malnutrition; assessing nutritional requirements; defining and implementing appropriate nutrition interventions while avoiding ineffective and potentially harmful therapies; maintaining function and quality of life, and improving the ability to administer effective anticancer treatments. The gut should always be the preferred route for nutrient administration. Preoperative nutritional support is beneficial to the malnourished.